ANTICONVULSANT EFFECT OFBERBERIS ARISTATA ROOT EXTRACT IN MICE - GOEL, DIVYA (International Journal of Current Pharmaceutical Research, 2023)
Objective: Berberine is an isoquinolone alkaloid present in many plants and reported to possess anti-diabetic, hypolipidemic, anti-cancer, anti-bacterial, anti-pyretic, antiviral and anti-inflammatory effects. In addition, berberine can modulate neurotransmitter like N-methyl-D-aspartate (NMDA), serotonin and Nitric Oxide, thus can produce anticonvulsant effect. Methods: The seizures were induced in mice by maximal pentylenetetrazol and electroshock. The effect of root extract on seizures was compared with standard anticonvulsant agents, phenytoin and diazepam. Results: Theroot extract of berberine aristata suppressed duration of tonic convulsions in maximal electroshock-induced seizures while it delayed time of onset of seizure as well as significantly decreased the duration of myoclonic-jerks-in pentylenetetrazol-induced seizures. Further, the study also indicated that the root extract of berberine aristata also produced motor impairment at the antiseizure doses. Conclusion: The present study indicated that berberine exhibits anticonvulsant activity in both models and can be useful in epileptic patients.